Modern Approaches To Surgical Correction Of Congenital Diaphragmatic Hernia In Newborns - Belova, Maria Olegovna; Abelkhayrova, Alina Baktygereevna; Lungu, Tatiana; Karasev, Andrey Romanovich; Kurbanova, Rashidat Ismailovna; Vasil, Polina; Morozyuk, evna; Andriukova, Sofiia Viacheslavovna (Journal of Neonatal Surgery, 2025)
Congenital diaphragmatic hernia in newborns is one of the most severe forms of congenital pathology, which is characterized by displacement of abdominal organs into the thoracic cavity through a defect in the diaphragm. This condition is accompanied by a high mortality rate and frequent life-threatening complications, among which the most significant are respiratory failure and marked pulmonary hypoplasia. In recent decades, neonatal surgery has made significant progress in the diagnosis and treatment of congenital diaphragmatic hernia, but the problem of choosing the optimal methods of correction is still relevant. The scientific community continues to debate in which order and at what stage it is most appropriate to use emergency surgery, delayed intervention, endoscopic techniques, and assistive technologies such as extracorporeal membrane oxygenation. The present study reviews modern surgical approaches and technologies for the management of neonates with congenital diaphragmatic hernia. The data of domestic and foreign studies, including our own results of retrospective analysis of 60 patients treated in a specialised center of neonatal surgery for the last three years were analyzed. The main aim of the work was to reveal the effectiveness and expediency of different methods of surgical correction, as well as to determine the main factors influencing the outcome of the disease. The results demonstrate that the introduction of endoscopic methods and the use of extracorporeal membrane oxygenation in the most severe patients can reduce hospital mortality and the number of complications, provided timely diagnosis and multidisciplinary approach